e-Book Game Education Berbasis Ekoliterasi untuk Melatih Keterampilan Ekoliterasi Siswa: (Ecoliteracy-Based Game Education E-Book to Train Students' Ecoliteracy Skills) - Shamla, Sun; Wulandari, Fitria Eka (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2025)
This study aims to describe the effect of e-Book Game Education based on ecoliteracy to train students' ecoliteracy skills. This study used a type of Quasi Experimental method with a research design of Nonequivalent Control Group Design involving 2 classes, namely the experimental class and the control class. The research instrument is an ecoliteracy question as many as twelve items that include four indicators of ecoliteracy including; 1)knowing environmental problems 2)having an action strategy for environmental problems 3)being able to follow up on environmental problems 4)having quality in addressing environmental problems, which have been valid and reliable. The data analysis technique in this study used the N-Gain test and the Independent sample test. The results showed that there was an effect of increasing students' ecoliteracy skills, in the sense that the use of ecoliteracy-based Game Education e-Books could improve students' ecoliteracy skills which could be shown in the experimental class obtained a higher N-Gain value than the control class. The normality test of the experimental class and control class on the pretest-postest obtained normal results. In the homogeneity test the data obtained from the experimental class and control class are homogeneous. In the Independent sample test, the experimental class got significant value results. This can occur because the experimental class gets the treatment of using ecoliteracy-based e-Book Game Education. So, the use of e-Book Game Education based on ecoliteracy has an influence in improving students' ecoliteracy skills. Abstrak. Penelitian ini bertujuan untuk mendeskripsikan pengaruh e-Book Game Education berbasis ekoliterasi untuk melatih keterampilan ekoliterasi siswa. Penelitian ini menggunakan jenis metode Quasi Experimental dengan desain penelitian Nonequivalent Control Group Desain melibatkan 2 kelas yaitu kelas eksperimen dan kelas kontrol. Instrument penelitian yaitu soal ekoliterasi sebanyak duabelas butir soal yang mencakup empat indikator ekoliterasi diantaranya; 1) mengetahui permasalahan lingkungan 2) mempunyai strategi tindakan terhadap permasalahan lingkungan 3) dapat menindaklanjuti terhadap permasalahan lingkungan 4) memiliki kualitas dalam menyikapi permasalahan lingkungan, yang telah valid dan reliabel. Teknik analisis data pada penelitian ini menggunakan uji N-Gain dan uji Independent sample test. Hasil penelitian menunjukkan bahwa adanya pengaruh peningkatan keterampilan ekoliterasi siswa, dalam arti penggunaan e-Book Game Education berbasis ekoliterasi dapat meningkatkan keterampilan ekoliterasi siswa yang dapat ditunjukkan pada kelas eksperimen memperoleh nilai N-Gain lebih tinggi dari pada kelas kontrol. Uji normalitas kelas eksperimen dan kelas kontrol pada pretest-postest memperoleh hasil yang bersifat normal. Pada uji homogenitas data yang diperoleh dari kelas eksperimen dan kelas kontrol bersifat homogen. Pada uji Independent sample test kelas eksperimen mendapatkan hasil nilai yang signifikan. Hal ini dapat terjadi dikarenakan kelas eksperimen mendapatkan perlakuan penggunaan e-Book Game Education berbasis ekoliterasi. Maka, penggunaan e-Book Game Education berbasis ekoliterasi mempunyai pengaruh dalam meningkatkan keterampilan ekoliterasi siswa.